Assessment of Depression and Anxiety Among Public Health Students: A Cross-Sectional Study in University of Hail, Saudi Arabia - Kumar, Rakesh (Journal of Contemporary Medical Sciences, 2024)
Objective: The study aims to identify the socio-demographic and lifestyle factors associated with depression, and anxiety among public health students at the University of Hail in Saudi Arabia. Methods: The researchers collected responses from 446 participants using a convenience sampling approach through a cross-sectional quantitative research design. The collected data underwent analysis through descriptive statistics, focusing on socio-demographic and lifestyle factors. Additionally, the measure of association is used to verify the associations of these factors with depression and anxiety among public health students of the University of Hail in Saudi Arabia. Finally, the binary logistic regression is used to identify the impacts of various socio-demographic, and lifestyle factors on mild to severe anxiety and depression of these students. Results: The research proves that lower family income and bad relationships with classmates are significant demographic factors, while unsatisfied sleep, smoking habits, and symptoms ranging from mild to severe depression are lifestyle factors that contribute to heightened anxiety among public health students at the University of Hail in Saudi Arabia. Additionally, it was also found that transitional age (21-25 years) from socio-demographic factors, unsatisfied sleep level, smoking habit, and mild to severe symptoms of anxiety also cause significant increased depression among these students. Conclusion: The study concludes that students who are not satisfied with their sleep, and have a smoking status are more exposed to anxiety as well as depression as compared to non-smokers, and the students with satisfied sleep. Additionally, those students who are not good in relationships with their classmates, and have mild to severe symptoms of depression are exposed to anxiety significantly. Finally, those students having a transitional age of 21-25 years along with mild to severe symptoms of anxiety are significantly exposed to depression.